Sports and Cultural Volunteering: Competitive or Complementary Activities? - Kirstin Hallmann; Cristina Mu\~niz Artime (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2022)
While nonprofit organizations have traditionally been considered increasingly competing for resources, this paper mainly explores the potential mutual relationship between volunteering in sport and volunteering in culture. Drawing on 2014 data from the German Volunteer Survey, we estimated a bivariate probit model based on 27,293 observations. The findings suggested that sports and cultural volunteering were complementary activities. Thus, promoting volunteering in one of the domains positively affected volunteering in the alternative domain. Parental volunteering, religiosity, and education were primary drivers of both types of volunteering. However, differences in some determinants have also been found. For example, volunteering in culture was predominantly female, while male volunteers dominated sports.
Keywords: 300; Volunteerism; Time allocation; Altruism; Civic commitment